2018
DOI: 10.1177/1557988317748393
|View full text |Cite
|
Sign up to set email alerts
|

Sense of Coherence, Smoking Status, Biochemical Cardiovascular Risk Factors and Body Mass in Blue Collar Workers—Short Report

Abstract: The crucial cause of cardiovascular disorders is atherosclerosis developed by abnormal cholesterols levels or disorders affecting blood glucose. One of the best-known cardiovascular risk factors is also tobacco smoking. Simultaneously, sense of coherence (SoC) as a personal resource motivating to managing one’s own health behaviors, such as avoiding tobacco smoking, was reported to be protective against coronary heart disease. Such association was observed in white-collar workers but not in blue-collar workers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…In addition, the present study revealed that lower serum concentration of the peptide was characteristic for patients with more advanced CAD and also for those who were active smokers. As smoking is one of the most widely known risk factors of cardiovascular diseases [24], this data suggests that one of the mechanisms of the deleterious impact of smoking on blood vessels might be an inhibitor of CPA3 production. Thus, all these data together confirms a protective effect of this enzyme in CAD.…”
Section: Discussionmentioning
confidence: 82%
“…In addition, the present study revealed that lower serum concentration of the peptide was characteristic for patients with more advanced CAD and also for those who were active smokers. As smoking is one of the most widely known risk factors of cardiovascular diseases [24], this data suggests that one of the mechanisms of the deleterious impact of smoking on blood vessels might be an inhibitor of CPA3 production. Thus, all these data together confirms a protective effect of this enzyme in CAD.…”
Section: Discussionmentioning
confidence: 82%
“…It spurs to deal with one's own health behaviors, for example, healthy diet, regular physical activity, or keeping away from dangerous practices like smoking. [ 8 ] Individuals with low SoC are increasingly inclined to respond to worry with smoking. [ 9 ]…”
Section: Introductionmentioning
confidence: 99%